2016
DOI: 10.1177/2053019616662052
|View full text |Cite
|
Sign up to set email alerts
|

Ethics in the Anthropocene: A research agenda

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 69 publications
0
37
0
2
Order By: Relevance
“…(, pp. 5, 8) argue the Anthropocene renders previous moral frameworks inadequate because there has been “no biological adaption and no cultural learning” sufficient to guide action under such novel conditions; as they put it, “Talk of ethics renders banal a transition that belongs to deep time , one that is literally Earth‐shattering.” This categorical rejection has been critiqued for dismissing all cultural learning, especially non‐Western knowledge and norms, by fiat (Schmidt et al., ). There is another facet, however, to how Hamilton links novelty to morality.…”
Section: Anthropocene Challenges To Moral Geographymentioning
confidence: 99%
“…(, pp. 5, 8) argue the Anthropocene renders previous moral frameworks inadequate because there has been “no biological adaption and no cultural learning” sufficient to guide action under such novel conditions; as they put it, “Talk of ethics renders banal a transition that belongs to deep time , one that is literally Earth‐shattering.” This categorical rejection has been critiqued for dismissing all cultural learning, especially non‐Western knowledge and norms, by fiat (Schmidt et al., ). There is another facet, however, to how Hamilton links novelty to morality.…”
Section: Anthropocene Challenges To Moral Geographymentioning
confidence: 99%
“…Human-induced global changes, such as global warming and biodiversity loss, are seen as modifying the planetary system in ways and at a speed no single species has ever done before (Crutzen 2002). The emergence of the concept of the Anthropocene is essentially an expression of human reflections on humannature relationships: it has been suggested that in the Anthropocene, 'mastery of nature' as endeavoured by the Enlightenment has now been achieved through mastery over the planetary system itself (Schmidt, Brown, and Orr 2016).…”
Section: Human-nature Relationships In the Anthropocenementioning
confidence: 99%
“…to take responsibility for Planet Earth (Steffen et al 2011;Schmidt, Brown, and Orr 2016;Elmqvist et al 2013). Understandings of stewardship range from reformist to transformative interpretations (Mathevet, Bousquet, and Raymond 2018).…”
Section: Human-nature Relationships In the Anthropocenementioning
confidence: 99%
“…Schmidt et al (2016), num texto em que propõem uma agenda de investigação sobre ética no Antropoceno, salientam diversas ideias-chave, de que destacamos duas: i) o Antropoceno levanta novas questões éticas em relação à natureza das relações humanos-planeta Terra e ao modo como garantir a transição em direção a esses valores (ib. : 6); ii) em contextos marcados por contingências de larga escala e por processos de decisão complexos relacionados com problemas de ação coletiva, como sucede com o Antropoceno, é particularmente decisivo cultivar virtudes como a humildade, promover 'disposições de caráter' como a justiça, a honestidade (truthfulness) e a esperança, e cumprir, com responsabilidade, obrigações para com humanos e não-humanos que permitam controlar a evolução do sistema terrestre (ib.…”
Section: O Antropoceno Como Acontecimento Científicounclassified